Digital manufacturing and assembly systems in industry 4.0 - Kumar, K. (Kaushik), 1968-; Zindani, Divya, 1989-; Davim, J. Paulo (Boca Raton : Taylor & Francis, CRC Press, 2019)
Manufacturing, like other industries, is rising to the challenges imposed by aggressive consumer demands and the need for cost-effective processing that delivers quality in the fastest possible time. Fierce competition means that keeping abreast of new developments and applications in technology is essential if companies are to meet demands profitably and keep ahead of competitors. This book investigates the design and management of digital manufacturing and assembly systems for an efficient, flexible, and modular production of customized products using the I40 (industry 4.0)-enabling technologies. This book will also provide case studies covering modeling, simulation, and optimization. eBook includes color figures. Discusses how the advancement of data communication and storage through the Internet of Things (IoT) opens the possibilities of connecting sensors, robots, and devices Sheds light on how the human role in industry is decreasing due to the development of connected manufacturing floors, allowing them to take more control over the manufacturing processes, decisions, and even maintenance Covers the benefits from exploiting digital manufacturing, manufacturing enterprises, and what they expect to achieve Explains the important roles that modeling, simulation, and optimization play Investigates the design and management of digital manufacturing and assembly systems for an efficient, flexible, and modular production of customized products exploiting the I40 (industry 4.0)-enabling technologies
OCLC-licensed vendor bibliographic record.
Keywords: Manufacturing processes -- Data processing; Assembly-line methods -- Data processing; COMPUTERS / Database Management / Data Mining; TECHNOLOGY / Electricity; TECHNOLOGY / Engineering / Industrial